2000
DOI: 10.1159/000017234
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Modulates the Membrane- Disordering Effects of Beta-Amyloid Peptides in the Hippocampus: Specific Changes in Alzheimer’s Disease

Abstract: Cholesterol represents an important determinant of the physical state of biological membranes. In Alzheimer’s disease (AD) brains, specific changes in the distribution of cholesterol and its membrane-ordering effects take place. In the present study, membrane fluidity was investigated at the level of the hydrocarbon core and of the heads of the phospholipid bilayers using two different fluorescent probes. Hippocampal membranes of AD brains showed a reduced fluidity in the hydrocarbon core region only. Fluidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 34 publications
(59 reference statements)
7
70
1
4
Order By: Relevance
“…[3,5,[33][34][35][36]76,85,89,90,96,111,134]). Of particular interest are those studies that show that not only an increase in the level of cholesterol, but also in the level of the toxic metabolite, 24S-hydroxycholesterol (cerebrosterol) [32,64].…”
Section: Membrane Fluidity In Aging-cholesterolmentioning
confidence: 99%
“…[3,5,[33][34][35][36]76,85,89,90,96,111,134]). Of particular interest are those studies that show that not only an increase in the level of cholesterol, but also in the level of the toxic metabolite, 24S-hydroxycholesterol (cerebrosterol) [32,64].…”
Section: Membrane Fluidity In Aging-cholesterolmentioning
confidence: 99%
“…It has been reported that A␤ is able to form ionic pores (21). A␤ can destroy the structure of brain membranes (22) and may stimulate free radical production by interfering with the regulation of calcium homeostasis and cell enzymatic activity (23). A␤ can also alter the physical-chemical properties of neuronal membranes, including membrane fluidity, membrane lipid dynamics, and the activity of various membrane-bound proteins (24,25).…”
mentioning
confidence: 99%
“…A major focus on the use of diet, cholesterol lowering drugs and lifestyles is to increase neuron number and decrease the size of plaques in the brain with aging. The membrane interactions of Aβ require cholesterol for clearance and metabolism with the increase in the membrane cholesterol involved in the regulation of Aβ assemblies [125][126][127]. The role of caloric restriction in activation of HDAC genes which control membrane cholesterol and the role of phytosterols and phytostanols (Figure 4 [99][100][101][102] have become of central interest since membrane interactions with cholesterol and Aβ may be required for the clearance and metabolism of Aβ.…”
Section: Phytosterols and Cholesterol Homeostasismentioning
confidence: 99%